An Investigation of Reformulation Markers in English and Persian Linguistics Articles - Maryam Koukhaei; Shahram Naghshbandi (مطالعات زبانی و بلاغی)
Reformulation markers are a subset of meta-discourse markers by which the second statement expresses or explains the first statement from a different point of view to make it easier and more convenient for the audience to understand the message. The present research aims to investigate the frequency, function, and type of reformulation discourse markers in English and Persian corpora in linguistics to discover differences and similarities. The English and Persian texts each contain 50 randomly selected articles. Considering the congruence and suitability of Hyland's (2005) model with the scientific discourse, it was used to identify reformulation markers. Murillo's (2012) model was also used in two corpora to study the function of reformulation markers. The obtained quantitative results show that the frequency of reformulation markers in the English sub-corpus is more than in the Persian one. The most significant reformulation markers in the English sub-corpus belonged to "i.e.," and in the Persian sub-corpus is "/ya’ni/". Based on the form, 50 different reformulation markers were found in the overall corpora. The results show that the highest frequency of the reformulation markers function in two sub-corpora is related to the interpretation of explicit meaning (descriptions and specifications). The lowest frequency of the markers function links to implicit meaning (mathematical operations).